Landscape of Infiltrated Immune Cell Characterization in Uveal Melanoma to Improve Immune Checkpoint Blockade Therapy - Lv, Xiaohui; Ding, Min; Liu, Yan (Frontiers in Immunology, 2022)
Background: Numerous studies indicated that tumor-infiltrated immune cells (TIC) in microenvironment substantially linked to immunotherapy response and cancers prognosis. However, the systematic study of infiltrated immune cells characterization in Uveal melanoma for prognosis and immune checkpoint blockade therapy is lacking. Methods: UM datasets were extracted from open accessed resources (TCGA and GEO databases). The tumor-infiltrated immune cells in microenvironment were decoded by using CIBERSORT algorithm, which was further applied to classified UM patients into subgroups by an unsupervised clustering method. Boruta algorithm and principal-component analysis were used to calculate the TIC scores for UM patients. Kaplan-Meier curves were plotted to prove the prognostic value of TIC score. Besides, the correlations of TIC score with clinical features, mutated characteristics, and the immune therapeutic response were subsequently investigated. Results: As a result, we defined three subtypes among 171 UM patients according to the TIC profiles, and then calculated the TCI score to characterize the immune patterns for all patients. we discovered that high-TCI score patients with low BAP1 and high EIF1AX mutations have a better prognosis than low-score patients. Activation of immune inflammatory response and increasing of immune checkpoint related genes in high-TCI score may count for good prognosis and immunotherapy response. Three melanoma cohorts received immunotherapy proven that high-TCI score patients have substantially clinical and immune therapeutic improvements. Besides, several potential therapeutic agents were identified in low-TIC score group. Conclusion: Our study afforded a comprehensive view of infiltrated immune cells characterization to elucidate different immune patterns of UM. We also established a robust TIC-score signature which may work as prognostic biomarker and immune therapeutic predictor.